Magnetic nanostructured material as heterogeneous catalyst for degradation of AB210 dye in tannery wastewater by electro-Fenton process - Cruz, Daiane R.S.; de Jesus, Gleyce K.; Santos, Clecia A.; Silva, Wenes R.; Wisniewski, Alberto; Cunha, Graziele C.; Romão, Luciane P.C. [UNESP] (My University, 2021)
Degradation of the Acid Black 210 dye (AB210) in synthetic and industrial effluent samples was performed, for the first time, using a heterogeneous electro-Fenton (EF) process with a CoFe2O4/NOM magnetic hybrid catalyst (Hb200). The technique was compared with electrochemical oxidation using electrogenerated hydrogen peroxide (AO-H2O2). The catalyst was synthesized by the sol-gel technique, using water with a high content of natural organic matter (NOM) as an eco-friendly solvent. Analyses using XRD, FTIR, and TEM showed the formation of hybrid nanostructures with average size of 4.85 nm. Electrochemical assays were performed with a GDE/BDD electrode pair, electrogenerated H2O2, and current density of 45.4 mA cm−2. For the synthetic solution of AB210 at pH 3, the EF process presented higher efficiency, compared to AO-H2O2, with the optimum condition achieved using a lower mass of the catalyst (30 mg) and a higher concentration of the dye (55 mg L−1). The EF method also showed superior performance in the treatment of an industrial effluent with high organic load, at pH 6, with almost complete mineralization of AB210 (95%) in 7 h, while the AO-H2O2 process achieved 82% mineralization. The Hb200 hybrid maintained excellent catalytic activity during reuse in 3 cycles, with only 10% lower mineralization efficiency in the last cycle. GC-MS analysis showed that most of the contaminants in the effluent, including bis(2-ethylhexyl) phthalate, one of the most toxic, were eliminated or transformed after the EF treatment with Hb200.
Keywords: Azo dye; BDD anode; Cobalt ferrite; Effluent; Mineralization